1998
DOI: 10.1021/ma980748q
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Melting Temperature and Undercooling Dependence of the Spherulitic Growth Rate of Isotactic Polypropylene

Abstract: Studies of the temperature dependence of spherulitic growth rates, in the context of the Lauritzen−Hoffman secondary nucleation theory, and investigations of the crystallization time and temperature dependence of the melting behavior, in the context of the nonlinear Hoffman−Weeks (HW) extrapolation, are reported for isotactic polypropylene prepared with Ziegler−Natta catalysts. The quantitative agreement between estimations of the equilibrium melting temperature, T m, through an analysis of spherulitic growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
133
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(142 citation statements)
references
References 75 publications
7
133
1
1
Order By: Relevance
“…15 The popularity of this approach is a result of its simplicity, as only the experimental melting temperature of the crystallites formed at T c is required. Nevertheless, Marand and co-workers 16,17 recently discussed the validity of the basic premise of the linear Hoffmann-Weeks treatment: that is, the thickening coefficient for lamellae, g, taken as independent of T c and time. [18][19][20] As demonstrated by some results in the literature, [16][17][18][19][20][21] the linear extrapolation, when carried out for lamellar crystals exhibiting a constant g value, invariably underestimates T m 1 and leads to an overestimation of the g value.…”
Section: Melting Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…15 The popularity of this approach is a result of its simplicity, as only the experimental melting temperature of the crystallites formed at T c is required. Nevertheless, Marand and co-workers 16,17 recently discussed the validity of the basic premise of the linear Hoffmann-Weeks treatment: that is, the thickening coefficient for lamellae, g, taken as independent of T c and time. [18][19][20] As demonstrated by some results in the literature, [16][17][18][19][20][21] the linear extrapolation, when carried out for lamellar crystals exhibiting a constant g value, invariably underestimates T m 1 and leads to an overestimation of the g value.…”
Section: Melting Behaviormentioning
confidence: 99%
“…Nevertheless, Marand and co-workers 16,17 recently discussed the validity of the basic premise of the linear Hoffmann-Weeks treatment: that is, the thickening coefficient for lamellae, g, taken as independent of T c and time. [18][19][20] As demonstrated by some results in the literature, [16][17][18][19][20][21] the linear extrapolation, when carried out for lamellar crystals exhibiting a constant g value, invariably underestimates T m 1 and leads to an overestimation of the g value. In fact, the HoffmannWeeks procedure does not account for the significant contribution to the difference between the melting and crystallization temperatures that arises from the temperature dependence of the fold surface free energy and the thickness increment above the minimum (thermodynamic) lamellar thickness.…”
Section: Melting Behaviormentioning
confidence: 99%
“…Their proposed method is hereafter called the "data-fitting" procedure. So far, this method has been successfully applied to the cases of poly(pivalolactone) [31] and its blends [31,32], isotactic polystyrene [33], poly(l-lactide-co-meso-lactide) copolymers [34], and isotactic polypropylene [35].…”
Section: Further Discussion On the T 0 M Value Used In The Analysismentioning
confidence: 99%
“…By assuming that the LH secondary nucleation theory can be applied to describe the temperature dependence of the growth rate data of polymers, other than that of polyethylene which is the basis for the development of theory, and that the measured growth rate data is of high quality, the true T 0 m value for the polymer of interest is taken as the value which results in the ratio of the corresponding nucleation exponents of 2.0. Xu et al [35] applied both the alternative approaches of the data-fitting procedure on the growth rate data of isotactic polypropylene, and found that the resulting T 0 m values from both approaches are comparable (ca. 215ЊC).…”
Section: Further Discussion On the T 0 M Value Used In The Analysismentioning
confidence: 99%
“…When the lamellar thickness for GT is determined at room temperature, an increase of the crystal height can occur during melting. A correct extrapolation is only possible for the HW method when the thickening coefficient is independent of the crystallization temperature, i.e., only samples crystallized at different temperatures, but with the same value for c, can be used to correctly determine T m0 [51].…”
Section: Flow-induced Crystallization Experimentsmentioning
confidence: 99%